Time and Measures of Success: Interpreting and Implementing Laudato Si’ - Grey, Carmody Teresa Sinclair (New blackfriars, 2020)
Laudato Si’ contains a prophetic vision of what time is and is for. It challenges development organisations to think critically about the way they conceive ‘progress’, the way they measure their ‘success’. In doing so, it invites them to ask how they express in their activity a particular conception of the meaning of time. This paper argues that Laudato Si’ proposes a vision of time which is theological, teleological, dialectical and contemplative, and that it is this vision which underpins its contrast between true and false notions of progress. The paper seeks to articulate a foundation for the formulation of authentic ‘measures of success’ that are expressive of this understanding of time, and to imagine what the organisational implications of such measures might be.